Liquid–liquid extraction of biopharmaceuticals from fermented broth: trends and future prospects - dos Santos, Nathalia Vieira [UNESP]; de Carvalho Santos-Ebinuma, Valéria [UNESP]; Pessoa Junior, Adalberto; Pereira, Jorge Fernando Brandão [UNESP] (Wiley, 2018)
Biopharmaceuticals are one of the most important groups of biotechnological products, representing one-quarter of all pharmaceutical sales and providing suitable and efficient medical care for many previously untreatable diseases. However, their production and purification usually require complex processes, resulting in extremely expensive final products. Thus, the development of newer, simpler and cheaper methods for biosynthesis and purification of these biocompounds, as well as proper integration between these stages, are crucial to reduce their commercial costs and to increase the scale of biopharmaceuticals' medical use. One solution for this concern relies on the proper integration between upstream and downstream processing applying liquid–liquid extraction systems as an intermediate stage. Recently, several works reported that a proper choice of liquid–liquid systems such as aqueous biphasic systems (ABS) can be a suitable platform to simplify, reduce the number of the downstream stages, improve the recovery and purification yields and, consequently, decrease biopharmaceuticals' manufacturing costs. This review will explain the general concept of biopharmaceuticals, their main production and purification methods, particularly, exploring the use of ABS as effective and integrative platforms for their recovery and purification, and providing further insights into the future trends and prospects in the field. © 2017 Society of Chemical Industry.
Keywords: aqueous biphasic systems; biopharmaceuticals; downstream process; fermentation; liquid–liquid extraction